2013
DOI: 10.1371/journal.pone.0077643
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Human MDM2-C Is Highly Expressed in Human Cancers and Functions as a p53-Independent Growth Activator

Abstract: Human cancers over-expressing mdm2, through a T to G variation at a single nucleotide polymorphism at position 309 (mdm2 SNP309), have functionally inactivated p53 that is not effectively degraded. They also have high expression of the alternatively spliced transcript, mdm2-C. Alternatively spliced mdm2 transcripts are expressed in many forms of human cancer and when they are exogenously expressed they transform human cells. However no study to date has detected endogenous MDM2 protein isoforms. Studies with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 62 publications
(78 reference statements)
2
40
0
Order By: Relevance
“…Interestingly, although the MDM2-A variant has a protective function in the p53 wild-type background, it can contribute to tumor progression in a p53-null background (114). In one study from 2013, similar p53-independent transforming activity has been found in another MDM2 splice variant, MDM2-C (115). …”
Section: Mdm2 and Mdmx In Human Cancermentioning
confidence: 52%
“…Interestingly, although the MDM2-A variant has a protective function in the p53 wild-type background, it can contribute to tumor progression in a p53-null background (114). In one study from 2013, similar p53-independent transforming activity has been found in another MDM2 splice variant, MDM2-C (115). …”
Section: Mdm2 and Mdmx In Human Cancermentioning
confidence: 52%
“…Okoro et al . reported that the MDM2‐C protein was highly expressed in human cancers and functioned as a p53‐independent growth activator . These data provide evidence that most MDM2 isoforms can contribute to tumor development in vivo .…”
Section: Mdm2mentioning
confidence: 54%
“…60 Okoro et al reported that the MDM2-C protein was highly expressed in human cancers and functioned as a p53-independent growth activator. 61 These data provide evidence that most MDM2 isoforms can contribute to tumor development in vivo. The outstanding difference in the activity of MDM2 splice variants in vivo (accelerated tumorigenesis) and cultured cells (inhibition of cell growth) can be explained by the possibility that the MDM2 splice variants act as oncogenes, and their forced expression triggers growth arrest in primary cells while they promote cell proliferation in cancer cells where the Arf-p53 pathway is inactivated.…”
Section: Functions Of Mdm2 Isoformsmentioning
confidence: 68%
“…Certain miRNAs can work as specific markers for prostate cancer by contributing towards the deduction of its classification, tumor grade, or differential diagnosis against benign prostate disease (Peter, 2009;Donnem et al, 2012). MDM2 was initially cloned from BALB/3T3 cells, and is highly expressed in pulmonary, breast, and colon cancers (Okoro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%